2012
DOI: 10.1002/cssc.201100641
|View full text |Cite
|
Sign up to set email alerts
|

New Insights from Microcalorimetry on the FeOx/CNT‐Based Electrocatalysts Active in the Conversion of CO2 to Fuels

Abstract: Fe oxide nanoparticles show enhanced electrocatalytic performance in the reduction of CO(2) to isopropanol when deposited on an N-functionalized carbon nanotube (CNT) support rather than on a pristine or oxidized CNT support. XRD and high-resolution TEM were used to investigate the nanostructure of the electrocatalysts, and CO(2) adsorptive microcalorimetry was used to study the chemical nature of the interaction of CO(2) with the surface sites. Although the particles always present the same Fe(3)O(4) phase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
59
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 50 publications
(63 citation statements)
references
References 43 publications
2
59
1
1
Order By: Relevance
“…Fig. 6 reports a scheme of the assembled electrodes-membrane element of the EL-PEC solar cell, with a picture of the assembly from the electrocatalyst side anda HAADF-STEM (high-angle annular dark field scanning transmission electron microscopy) image for Fe/CNT catalyst (a) with a zoom (b) on the small particles present on the external surface of carbon nanotube (by HRTEM -high resolution transmission electron microscopy) [163]. Fig.…”
Section: Development Of the Electrocatalyst For Co 2 Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fig. 6 reports a scheme of the assembled electrodes-membrane element of the EL-PEC solar cell, with a picture of the assembly from the electrocatalyst side anda HAADF-STEM (high-angle annular dark field scanning transmission electron microscopy) image for Fe/CNT catalyst (a) with a zoom (b) on the small particles present on the external surface of carbon nanotube (by HRTEM -high resolution transmission electron microscopy) [163]. Fig.…”
Section: Development Of the Electrocatalyst For Co 2 Reductionmentioning
confidence: 99%
“…The presence of N functionalities on the CNT, particularly quaternary graphitic N species, allows changing significantly the heat of chemisorption of CO 2 [163].…”
Section: Development Of the Electrocatalytic Electrodementioning
confidence: 99%
“…44,92,113,120,125,126 Palladium as the only metal supported can lead to other conclusions. 42,127,128,134,135 As reported earlier, the research in recent years focused on the oxidation state of Pd, which is a crucial parameter along with the PdAu or Pd-Pt alloying and the support for the metals. The oxidation state of Pd in the bimetallic catalysts (or in the monometallic ones) can be related to the initial formation of H 2 O 2 , but also its sequential hydrogenation.…”
mentioning
confidence: 99%
“…Several studies indicated that CNTs are more efficient supports for higher alcohol synthesis [8,[17][18][19][20] than conventional metal oxides such as Al 2 O 3 [21], and SiO 2 [5,9,22]. On the other hand, N-doping of nanocarbons is known to efficiently increase the dispersion of noble metal nanoparticles [17,[23][24][25].…”
Section: −1mentioning
confidence: 99%